La mémoire littéraire dans quelques Mémoires de la Révolution - Anne Coudreuse (Itinéraires)
Memoirs are referential texts, but this does not mean that they exclude memory from fictional or autobiographical works, in which the historical dimension is far less prominent. In particular, the Rousseau model comes to mind with its evolution in the writings of late 18th century and early 19th century memoirists. Questioning memory and literary culture in the Memoirs of the Revolutionary period in France is done differently, depending on wether the memoirist is already a writer, and a novelist at that, such as Louvet de Couvray, or the memoirist is someone without experience in writing until History incites them to put pen to paper, such as Élisabeth Vigée Le Brun, who felt the need to write her Souvenirs. The question must also be asked in terms of legitimacy: do quotations, references, allusions, etc., allow for authority to be established and do they serve as legitimizing devices, or are they part of a common source from which we can automatically draw?